UPT BLK Surabaya Quality Assurance Strategy In Increasing The Relevance Of Training To Industry Needs - Alfi Nurhasanah (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
This study aims to analyze the quality assurance strategy implemented by the UPT Job Training Center (BLK) Surabaya in increasing the relevance of training to industrial needs. The research approach uses a descriptive qualitative method, with data collection techniques through observation, interviews with the Head of Training and Certification (Mr. Yudo Sembodo Hastoro Langgeng, S.Kom.), and examination of internal documents of the institution. The results of the study show that UPT BLK Surabaya has implemented a training quality assurance system based on the Indonesian National Work Competency Standards (SKKNI) and is oriented to the real needs of the industrial world. The main strategies include mapping the quality of training, the preparation of quality improvement plans based on cooperation with FKLPID and the business world and industry, the implementation of quality fulfillment through instructor and participant certification, monitoring and tracer studies of alumni, to the establishment of new standards that are adaptive to industry trends, including the green job sector. The main challenges faced include limited facilities and budgets, as well as the speed of industrial technological change that often exceeds the curriculum renewal process. Nevertheless, UPT BLK Surabaya's commitment to continue to strengthen collaboration with the business world and industry and integrate digital technology in training has proven to be effective in increasing the competitiveness of graduates. These findings confirm that a systematic, data-based, and responsive quality assurance system is key to producing a competent and job-ready workforce.